2018
DOI: 10.1039/c7lc01113j
|View full text |Cite
|
Sign up to set email alerts
|

3D printed high density, reversible, chip-to-chip microfluidic interconnects

Abstract: Our latest developments in miniaturizing 3D printed microfluidics [Gong et al., Lab Chip, 2016, 16, 2450; Gong et al., Lab Chip, 2017, 17, 2899] offer the opportunity to fabricate highly integrated chips that measure only a few mm on a side. For such small chips, an interconnection method is needed to provide the necessary world-to-chip reagent and pneumatic connections. In this paper, we introduce simple integrated microgaskets (SIMs) and controlled-compression integrated microgaskets (CCIMs) to connect a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 19 publications
0
62
0
Order By: Relevance
“…Second, we used a 4% PEGDA solution: we found that 3% PEGDA was not sufficient to eliminate the undesired migration of analyte while 5% PEGDA tended to block the channels and prevent fluid flow. While these COC devices are compatible with standard 2D micromachining, we note that it is also feasible to 3D print microfluidic devices from PEGDA [37][38][39]. These 3D printed devices may be appealing for future analyses to avoid this photografting step.…”
Section: Resultsmentioning
confidence: 99%
“…Second, we used a 4% PEGDA solution: we found that 3% PEGDA was not sufficient to eliminate the undesired migration of analyte while 5% PEGDA tended to block the channels and prevent fluid flow. While these COC devices are compatible with standard 2D micromachining, we note that it is also feasible to 3D print microfluidic devices from PEGDA [37][38][39]. These 3D printed devices may be appealing for future analyses to avoid this photografting step.…”
Section: Resultsmentioning
confidence: 99%
“…The current resolution of commercial 3D printing technologies limits the integration of large numbers of connectors and multiplexers. However, custom 3D printer and resin 42 have been made demonstrating the integration of 88 connectors per mm 2 , with a feature resolution <20 μm 43,44 , which could allow making MFM with higher resolution and higher density applications, and serve many more applications in the life sciences.…”
Section: Discussionmentioning
confidence: 99%
“…For our printer and this resin, surface roughness has previously been characterized using optical profilometry with prints at various exposure times [ 22 ]. For all exposure times tested (600–1200 ms), the RMS surface roughness was less than 100 nm, typically 55–60 ± 15 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has developed an SLA 3D printer, as well as a custom resin formulated specifically for creating truly microfluidic structures with this printer [ 20 ], and we have made small (18 × 20 µm) microfluidic channels [ 21 ], as well as fluid control systems involving pumps and valves [ 22 ]. To make the smallest channels, an edge compensation technique was employed which overexposed the pixels at the channel edge to make it narrower [ 21 ].…”
Section: Introductionmentioning
confidence: 99%